"Defund the police:" Perceptions among protesters in the 2020 March on Washington. Issue 1 (20th January 2022) - Cobbina‐Dungy, Jennifer; Chaudhuri, Soma; LaCourse, Ashleigh; DeJong, Christina
Abstract: Research summary : Using qualitative interviews, this study examines how protesters with varying levels of commitment to the Black Lives Matter movement perceive the slogan defund the police. Findings indicate while a small number had reservations regarding the term, the vast majority of protesters associate defunding as a two‐step process that starts with reduction of police budgets, followed by reallocation of these resources toward much needed services in the very communities the departments serve. Findings also revealed prior engagement with the Black Lives Matter movement, and the level of commitment of participants did play an important role in being able to provide nuanced context to the call for action. Policy implications : Implementation of reduction of police budgets indicates a need to reimagine the role and function of police in most affected communities. In addition, there is a need to reinvest in local resources that would provide the much needed support toward marginalized communities. Further, social movement organizations should partner with corporate brands and advertising agencies to effectively promote their goals and slogans toward a diverse range of audience in media.